Effect of creep, shrinkage and cracking on time dependent behaviour of RC structures - Haldar, Ayan; Gopinath, Smitha; Palani, G.S.; Iyer, Nagesh R. (Journal of Structural Engineering, 2025)
This paper proposes a numerical model to compute the time dependent behaviour of reinforced concrete (RC) structures accounting for tension softening. The interaction of creep, shrinkage and the tension softening effect is incorporated in the nonlinear analysis through a finite element model. The creep of the concrete is taken into account using creep compliance function in the form of Dirichlet Series while shrinkage is modelled using ACI 209 recommendations. The hyperbolic tension softening curve is proposed to consider the time-dependent effects of reinforced concrete in cracked phase. An iterative solution technique using Newton-Raphson method has been employed in the nonlinear analysis. Proposed model has been validated by studying the nonlinear response of a simply supported singly reinforced beam and a corner supported square slab under sustained loading with several time intervals. For singly reinforced beam, the increase in midspan deflection with time and variation of midspan deflection at various ages of loading has been computed. For the corner supported slab, the centre point deflection v/s time graph is computed for various loading. From the analysis, it is observed that the computed midspan displacements at various time intervals are in good agreement with corresponding experimental results.